Urban space spatiality in Purwokerto, Jawa Tengah: Case from Gedung Soetedja - Wiman Rizkidarajat; Arizal Mutahir; Isna Hanny; Ismael Caceres Correa (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
This article attempts to trace the spatiality of urban space in Purwokerto using Lefebvian theory. The main urban space in this article is Gedung Soetedja which was previously located on Jalan Gatot Soebroto, Purwokerto Barat. As long as it was an urban space, the central discourse of Gedung Soetedja was underground music which was born from the movements of urban youth in Indonesia in the early 2000s. The method used in this article is descriptive qualitative. The data was obtained through interviews with 2 actors and organizers of underground gigs in early 2000s, 2 actors of a youth collective called Heartcorner Collective, 2 cafe owners who were often used to Heartcorner Collective organize gigs (micro scale underground music concert), and 1 journalist. This data was obtained from May-August 2023. The findings of this article are the efforts of a collective, the Heartcorner Collective, to create urban spatiality through re-reading underground music discourse, placemaking, and spatiality of urban spaces. Furthermore, this article also presents things that caused Gedung Soetedja to lose its inclusiveness when Pemerintah Daerah Kabupaten Banyumas moved it to its new location.